(untitled) (Journal of Rangpur Medical College, 2023)
Artificial intelligence (AI) has significant potential in the field of gastroenterology by aiding in the diagnosis, treatment, and monitoring of patients. With its ability to analyze medical images and patient information, identify risk factors, and enable remote consultations and monitoring, AI can improve accuracy, efficiency, and personalized care for patients. This advancement in technology has the potential to revolutionize patient outcomes. As further research is conducted, the possibilities for AI in gastroenterology will continue to expand, ultimately leading to improved patient outcomes. J Rang Med Col. September 2023; Vol. 8, No. 2: 48-52